Treatment of medial humeral epicondyle fractures in children using absorbable self-reinforced polylactide pins - Su, Yuxi (Medicine (Baltimore), 2020)
The best treatment for medial humeral epicondyle fractures in children has been debated. In case of incarceration of the epicondylar fragment, particularly after elbow dislocation, several materials are used for fixation, including Kirschner wires (K-wires), metallic compression screws, tension band wire, and suture anchors. Herein, we introduce a new fixation material: the absorbable self-reinforced polylactide (SR-PLA) pin. The aim of the study was to prove the feasibility of a new fixation material (absorbable SR-PLA pins) for the treatment of medial epicondyle fracture in children. Thirty-two patients who underwent surgery in our hospital from August 2007 to January 2012 were retrospectively analyzed. The patients were divided into group A (K-wires) and group B (absorbable SR-PLA pin). Group A comprised 11 males and 4 females, aged 8 to 14 years (average, 12.6 years), with 12 patients with elbow dislocation. Group B comprised 13 males and 4 females, aged 7 to 15 years (average, 11.8 years), with 13 patients with elbow dislocation. The same approach was used for all patients by the same team of surgeons, and all the patients were followed up for over 12 months. In all patients, rehabilitation training was started after 3 weeks. The Broberg and Morrey elbow scale was used to evaluate elbow function at follow-up. Four patients from group A developed pin-track infections that gradually resolved after removal of the K-wires, whereas no infections occurred in group B. One patient refractured her humerus after K-wire removal. Using the Broberg and Morrey elbow scale, outcomes in group A were classified as excellent in 5 patients (33.33%), good in 7 patients (46.67%), fair in 2 patients (13.33%), and poor in 1 (0.07%). Group B outcomes were scored as excellent in 12 patients (70.58%), good in 4 (23.53%), and fair in 1 (0.06%) and no patient (0.00%) had a poor outcome. The average Broberg and Morrey score for group A was significantly lower than that for group B (83.27 ± 7.02 vs 95.21 ± 5.04; P = .0238). Absorbable SR-PLA pins can be safely used for medial epicondyle fractures in children. Our results indicate that SR-PLA pins are associated with better short-term functional outcome than K-wires. Level of evidence: III